Family History of Cancer Rather Than p53 Status Predicts Efficacy of Pegylated Liposomal Doxorubicin and Oxaliplatin in Relapsed Ovarian Cancer. Issue 6 (1st July 2009) - Nicoletto, Maria Ornella; Bertorelle, Roberta; Borgato, Lucia; De Salvo, Gian Luca; Artioli, Grazia; Lombardi, Giuseppe; Zustovich, Fable; Marcato, Raffaella; Parenti, Anna; Montagna, Marco; Donach, Martin E.
Abstract : Background: The aim of the study was to assess the efficacy of pegylated liposomal doxorubicin (PLD) and oxaliplatin in patients affected by relapsed epithelial ovarian cancer with a family history of BRCA and p53 mutations. Methods: Seventy-two women received a median of 7.5 courses of PLD at 30 to 35 mg/m 2 plus oxaliplatin at 70 mg/m 2, and associations between BRCA1/2 and TP53 status and overall survival (OS) were determined. Thirty-eight had a short platinum-free interval (PFI; <12 months), and 34 had a long PFI (≥12 months). Results: Nine patients had BRCA1 mutations, and 1 had a BRCA2 mutation. Platinum sensitivity was associated with OS ( P = 0.0001). At a median follow-up of 9.3 months, objective response rate, median time to progression, and OS were 47.3%, 5.8 months, and 12.9 months, respectively, in short PFI compared with the 76.5%, 11.5 months, and 47.7 months in long PFI. p53 status did not correlate to these parameters. The median time to progression was 11.5 months for high-risk patients versus 6.5 months for patients with sporadic cancer ( P = 0.0188), and the median OS from the start of treatment was 48.7 and 16.2 months ( P = 0.0032), respectively. Toxicity was mostly grade 1 or 2. Conclusions: High response rates in the long-PFI patients indicate that this treatment is beneficial and well tolerated. Platinum sensitivity and positive family history and/or a BRCA1 / BRCA2 mutation are a useful predictor of response.